Analisis Realisasi Penerimaan Pajak Reklame dan Pengaruhnya Terhadap Pendapatan Asli Daerah Kabupaten Batang Hari Periode 2006-2015 - Sri Rosmawati; Fadhila Rizqiah (Universitas Batanghari Jambi, 2019)
This research was conducted to find out how the development of Batang Hari Regency Advertising Tax revenue, how the Development of Batang Hari Regency's Original Revenue, and how the Effect of Advertisement Tax Receipts Against the Local Revenue of Batang Hari Regency for the period 2006-2015. Research results show (1) Development of Batang Hari Regency advertisement tax receipts for 2006-2015 The most significant increase in percentage occurred in 2010, which was 46.34%. (2) The development of the original revenue of the Batang Regency in 2006-2015 experienced fluctuations. Realization of the largest Revenue of Regional Original Revenue was achieved in 2014. (3) Admission of Advertising Taxes had a positive effect on the Local Revenue of the Batang Hari Regency. When the Advertising Tax is deemed constant, the Regional Original Income is 146,218,304. Every increase in Advertising Tax revenue will increase Regional Original Income by 8 percent. The determination coefficient (R2) is 0.547. This figure shows that the Regional Original Income is influenced by sebaar Advertising Taxes 54.7 percent. While the remaining 45.3 percent is influenced by other variables not used in this study.